Study on the process of medical waste disinfection by microwave technology. (1st August 2022) - Liu, Jie; Li, Haoru; Liu, Zhibo; Meng, Xiangwen; He, Yan; Zhang, Zhentao
Graphical abstract: Highlights: The microwave sterilization progress parameters were optimized by orthogonal test. Microwave sterilization screw conveying system for MW was built. The sterilization time has the most influence on the sterilization effect. Pass steam to control the temperature of the system in the range of 100 °C ∼ 120 °C. Abstract: Microwave sterilization technology is an environmentally friendly non-incineration disposal method for medical waste. The core sterilization technology of "microwave sterilization, steam makes the system heat up quickly" was adopted to build a microwave sterilization screw conveyor system that can continuously and dynamically type microwave sterilization. The platinum resistance temperature sensor is used to measure the temperature of the steam at the outlet of the system and the temperature of the material at the outlet. The microwave sterilization process for medical waste was studied on the microwave sterilization test platform, and the influence and regularity of three factors on the microwave sterilization effect were explored and the microwave sterilization process was optimized using the orthogonal test method. Bacillus subtilis var. black spore (ATCC 9372) was used as the detection object of microwave sterilization effect, and the sterilization rate was calculated by the total number of colonies after culture. The results show that, microwave sterilization time has the greatest influence on sterilization effect, the greater the microwave power, the longer the sterilization time, the higher the water content, the higher the sterilization rate. The orthogonal test results show that the optimal process parameters of the microwave sterilization system are the microwave power of 22 kW, the sterilization time of 480 s, and the moisture content of 90%, the sterilization rate is 99.9996%, the sterilization effect is good. When the microwave power is 25 kW or 28 kW, the sterilization time is 480 s or 600 s, and the water content is 90%, the sterilization rate is 100%. Considering the germicidal effect, equipment cost, saving power consumption, shortening the germicidal process time and other comprehensive factors, this process parameter can obtain the best benefit. It can be seen that the use of microwave sterilization technology to treat medical waste is fast and efficient, and does not produce dioxins and other harmful substances, safe and environmental protection, simple operation, excellent sterilization effect.